Pedagogical Views and Educational Activities of Ismail Gasprinsky - Хайруддинов, Мухиддин (Lietuvos istorijos studijos, 2023)
The article deals with the pedagogical and educational activities of the outstanding son of the Crimean Tatar people Ismail Gasprinsky (1851–1914). Accumulating the achievements of the advanced pedagogical practice of Europe, I. Gasprinsky acted as a spokesman for the need for socio-economic changes in the countries of the East. I. Gasprinsky spoke up for the synthesis of Muslim doctrine and the achievements of modern science, he created and led the Jadid pedagogical movement aimed at the transition from confessional and Russian civic education to the creation of a national secular education. All his life I. Gasprinsky was defending the interests of the Crimean Tatars, Mus- lims and societies living in conditions of colonial slavery. Gasprinsky was one of the most outstanding thinkers of the Turkic world. UNESCO declared 2014 the year of Ismail Gasprinsky for his contribution to education and philosophy. The study showed that the modern interest in I. Gasprinsky is caused by the increasingly unfolding globalization and the formation of an ecological-humanistic civilization, as a new form of preserving cultural diversity in its entirety.